Relating beta diversity of birds and butterflies in the Great Basin to spatial resolution, environmental variables and trait‐based groups. Issue 3 (4th December 2018) - Yen, Jian D. L.; Fleishman, Erica; Fogarty, Frank; Dobkin, David S.
Abstract: Aim: We sought to characterize spatial and temporal beta diversity of birds and butterflies in the Great Basin (western U.S.A.) and to determine whether the magnitude of beta diversity was associated with spatial resolution, trait‐based groups or local environmental variables. Location: Central and western Great Basin, western U.S.A. Time period: 1995–2014. Major taxa studied: Birds and butterflies. Methods: We calculated temporal and spatial beta diversity of birds and butterflies at two spatial resolutions, points (birds) or transects (butterflies) and canyons (birds and butterflies). Points and transects corresponded to the spatial resolution of sampling, whereas canyons might be a more ecologically meaningful resolution. We partitioned beta diversity into turnover and nestedness components, and we calculated these components for entire assemblages and for trait‐based groups within assemblages. We used Bayesian hierarchical models to relate turnover and nestedness to spatial resolution, trait‐based groups and environmental variables. Results: Variation in the composition of bird and butterfly assemblages was primarily associated with turnover. Species composition was more consistent at the resolution of canyons than at finer spatial resolutions. The species composition of birds changed more through space than through time, and spatial turnover of bird species tended to be higher than that of butterfly species. There were few strong associations of turnover and nestedness with environmental variables, and none with trait‐based groups. Main conclusions: Our results suggest that the identities of bird and butterfly species vary at locations within canyons among years but are less variable among canyons. Decreases in temporal turnover as spatial resolution increases suggest that, at fine spatial resolutions and among years, bird and butterfly species in the Great Basin might acquire resources somewhat opportunistically rather than via strong interspecific competition (birds and butterflies) or site tenacity to breeding territories (birds).